Paulo Freire's Educational Philosophy and Implications in the Kurdistan Region of Iraqi Education - Karwan Kakabra Kakamad; Jaafar Omer Ahmed; Hakeem Abubaker Ali (Journal of Philology and Educational Sciences, 2025)
Paulo Freire was one of the most influential educational theorists of the 20th century, and his ideas have continued to shape pedagogical practices around the world. This paper explores how Freire’s educational philosophy, principally his critique of the "banking concept" of education, can be applied to the current educational system in the Kurdistan Region of Iraq. A survey of ten-item questionnaire was conducted with 258 university students across Kurdistan region. The findings reveal that a significant majority (94%) view their learning experience as fitting the banking model, in which students passively receive information from teachers. These results raise significant concerns regarding the effectiveness of the current system and suggest a need for reforms grounded in critical pedagogy. The paper concludes by offering practical recommendations for incorporating Freire’s ideas into local educational practices, with a focus on encouraging critical thinking and student engagement.